Analisa Laporan Keuangan Sebagai Dasar Penilaian Kondisi Kinerja Manajemen PT. Ultrajaya Milk Industry & Trading Company Tbk. - Dwi Dayanti Oktavia; Desvilian Larasati Rachim (STIE Kertanegara Malang, 2019)
This research is conducted to know the performance of management of PT. Ultrajaya Milk Industry & Trading Company, Tbk. The method used in the form of quantitative descriptive that is by collecting, presenting, and analyzing data from the company using the analysis of liquidity and solvency ratios to the financial statements of PT. Ultrajaya Milk Industry & Trading Company, Tbk. period 2013, 2014, 2015, 2016 and 2017. Based on research that has been done, it can be concluded that PT. Ultrajaya Milk Industry & Trading Company, Tbk in the year 2013 - 2017 has a very good performance. Seen from the increase in the average number of Current Ratio for 5 years by 43%, Quick Ratio by 43% and Cash Ratio by 40%. The optimum performance of the company according to the calculation of liquidity ratio occurred in 2016 which increased 100% from each ratio.Based on the calculation of Solvency for 5 years decreased DTAR by 2%, DTER by 4% and TIE experienced an average increase of 158 times. Where the ratio of this ratio proves that the company is very solvable.Sedangkan Rentability ratio shows that the company is able to generate profits, although with a small percentage of less than 50%. Researchers also conduct an assessment of financial management performance of PT. Ultrajaya Milk Industry & Trading Company, Tbk. during the year 2013 - 2017 when compared with similar companies. And obtained the result that PT. Ultrajaya Milk Industry & Trading Company, Tbk has superior performance than PT. Mayora Indah Tbk and PT. Indofood Sukses Makmur, Tbk. with the rate ratio always above the industry average.